La tradición de los monigotes en la ciudad de Machala, desde una perspectiva artística contemporánea. - Mendoza Poma, Cecilia Florentina (2015)
Within the next artistic project you can appreciate the history and tradition of the puppets in the city of Machala and how these have been changing over time. Research aiming a proposal from a critical look at the behavior of society on this tradition, using the technique of photography and video art as a record of their production will be designed. For this process was counted with the various methodological techniques tales like the Field Research, The literature through the use of files and photos as well Interviews with individuals exercising work named. Since the preparation of masks to the simple puppets of sawdust and of course the most elaborate in a more detailed Those Who today represent the UN recognized character in the middle. At that was obtained as Main results of the various experiences in advancing the present and describe conclusion is achieved, from A Critical and perceptive way to the viewer, the comprehensive development of the work against the use of Philosophical Concepts. As Recommendation belong to which project There Transition explain the fact that exists within the cultural tradition of the puppets in the city of Machala.